Thinking with Sloterdijk. Anthropotechnics, exercise, and education - Pulido-Cortés, Oscar; Universidad Pedagógica y Tecnológica de Colombia; Espinel, Oscar ; Corporación Universitaria Minuto de Dios; Cárdenas Obregón, Karen Andrea ; Universidad Pedagógica y Tecnológica de Colombia; Díaz Bernal, Juan Guillermo ; Universidad Pedagógica y Tecnológica de Colombia; Castro Patarroyo, Lizeth Ximena; INEM Carlos Arturo torres; Pérez Burgos, Diego Fernando ; Fundación Pedagógica Rayuela; Mora Vanegas, Diana Ximena; Alba Talero, Miguel Ángel; Montaña Contreras, Deiscy Soraya ; Universidad Pedagógica y Tecnológica de Colombia; Cruz Vargas, Iván Darío ; Universidad Pedagógica y Tecnológica de Colombia; Ojeda Suárez, Manuel Alejandro ; I.E. departamental Tierra de promisión; Vargas, Ingrid ; Corporación Universitaria Minuto de Dios; et al. (UPTC Editorial, 2021)
This book addresses the texts of Peter Sloterdijk searching for theoreticalmethodological notions to reflect on the problems of education, pedagogy, and philosophy itself from other perspectives. By assuming philosophy as a matter of problematization, notions such as anthropotechnics and exercise emerge to shape new questions and new ways of asking in the field of philosophy of education. Reading Sloterdijk’s texts leads to pieces of writing that inquire into the exercising forms involved in teaching, being a teacher, the learner, the learning, and the bodies sculpted by sports practices, writing, and reading. Through these techniques, spaces and mechanisms, human beings become what they are: human. Working on problems under this theoretical-methodological perspective means exploring the potential of the tools to use them and even to develop otherapplications, forms, and possibilities. However, this use must be supported by the review, the knowledge, and the preparation of tools, which is the purpose of this book, based on the approach to Sloterdijk’s thought